2016
DOI: 10.1680/jgele.16.00106
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on pull-out capacity of torpedo anchors in clay

Abstract: This paper reports the results from dynamic finite-element analyses undertaken to provide insight into the behaviour of torpedo anchors during pullout in non-homogeneous clay. The results were validated against field data prior to undertaking a parametric study, exploring the relevant range of parameters in terms of installation effect, impact velocity, anchor geometry, padeye position, pullout angle. Installation method (e.g. quasi-static and dynamic installation) has shown significant influence on the vertic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Generally, the deeper embedment depths of DIAs guarantee higher pullout capacity due to the increase in shear strength (Richardson et al, 2009;O'Loughlin et al, 2009O'Loughlin et al, , 2013Kim and Hossain, 2016). In addition, several studies have demonstrated that the lowered padeye position may allow the anchor to embed further (through diving) during pullout (Tian et al, 2014;Liu et al, 2016b;Zhao et al, 2016;Kim and Hossain, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the deeper embedment depths of DIAs guarantee higher pullout capacity due to the increase in shear strength (Richardson et al, 2009;O'Loughlin et al, 2009O'Loughlin et al, , 2013Kim and Hossain, 2016). In addition, several studies have demonstrated that the lowered padeye position may allow the anchor to embed further (through diving) during pullout (Tian et al, 2014;Liu et al, 2016b;Zhao et al, 2016;Kim and Hossain, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…3D LDFE analyses were carried out using the coupled Eulerian-Lagrangian (CEL) approach in the commercial Finite Element (FE) package ABAQUS/Explicit (Version 6.12) [26] [27][28][29][30][31][32][33][34][35] have investigated various geotechnical problems using the CEL approach and provided evidence that it is applicable to solve problems involving large deformations. Extensive background information about CEL, spudcan installation and footprint modelling can be found in Jun et al, Zheng et al and Hu et al [23,24,35,36]; this information is not repeated here.…”
Section: Numerical Analysismentioning
confidence: 99%
“…The simulation was fully integrated taking into account the disturbed soil conditions through installation of the anchor for the loading stage [19]. An inclined loading, instead of an inclined displacement, was applied at the anchor padeye ( a ) to obtain apparent anchor trajectory.…”
Section: Analysis Detailsmentioning
confidence: 99%